Effects on Inter-Personal Memory of Dancing in Time with Others - Woolhouse, Matthew H.; Tidhar, Dan; Cross, Ian (Frontiers in Psychology, 2016)
We report an experiment investigating whether dancing to the same music enhances recall of person-related memory targets. The experiment used 40 dancers (all of whom were unaware of the experiment’s aim), 2-channel silent-disco radio headphones, a marked-up dance floor, two types of music, and memory targets (sash colours and symbols). In each trial, 10 dancers wore radio headphones and one of 4 different coloured sashes, half of which carried cat symbols. Using silent-disco technology, one type of music was surreptitiously transmitted to half the dancers, while music at a different tempo was transmitted to the remaining dancers. Pre-experiment, the dancers’ faces were photographed. Post-experiment, each dancer was presented with the photographs of the other dancers and asked to recall their memory targets. Results showed that same-music dancing significantly enhanced memory for sash colour and sash symbol. Our findings are discussed in light of recent eye-movement research that showed significantly increased gaze durations for people observing music-dance synchrony versus music-dance asynchrony, and in relation to current literature on interpersonal entrainment, group cohesion and social bonding.